Adsorptive desulfurization of metal phthalocyanine functionalized poly-ionic liquids grafted to silica gel. (15th May 2018) - Zhang, Juan; Sun, Shuang; Bian, Yuhang; Li, Weikang; Liu, Ran; Zhao, Dishun
Graphical abstract: Metal phthalocyanine functionalized poly-ionic liquids grafted to silica gel were synthesized for adsorptive desulfurization of dibenzothiophene as adsorbent. Their performance of adsorptive desulfurization at room temperature and atmospheric pressure was better than other reported adsorbents. the regeneration of adsorbents doesn't need burning, and only need washing by solvent, the solvent can been recycled and reused by rectification. There aren't secondary pollution. Highlights: Metal phthalocyanine functionalized poly-ionic liquids was synthesized as adsorbent. The adsorptive desulfurization effect on DBT of P-4 was best by screening. The adsorption capacity of P-4 did not decrease obviously by reusing for 10 times. P-4 also has a good adsorption effect on different organic sulfur compounds. Abstract: Four metal phthalocyanines (Pc-4, 8, 12, 16) functionalized ionic liquids were polymerized on the surface of silica gel as adsorbent materials. They were characterized by FT-IR, BET, SEM and TEM measurements. The characterization results proved that the adsorbents were prepared successfully. Their adsorptive desulfurization performances to dibenzothiophene in model oil at room temperature and atmospheric pressure were investigated in detail. The results showed that the adsorptive desulfurization effect of P-4 was best. The optimal amount of adsorbent was 10 g/100 mL model oil. The maximum amount of DBT adsorbed was 52.41 mg/g, superior to some previously reported adsorbents. The adsorption equilibrium and kinetics of this adsorbent were also examined. The adsorption behavior fitted well to Freundlich isotherm model, pseudo-second-order kinetics model and Weber and Morris kinetics model. Adsorption and regeneration by solvent processes were performed 10 times, and the adsorption capacity of the adsorbent did not decrease obviously. P-4 also had a good adsorption effect on different sulfur compounds, and the order of removal was DBT > BT > 2-MTH > TH.